Coronary Artery Rupture Associated with Blunt Force to the Thorax: An Autopsy Report - Bhanu Kumar (Universitas Udayana, 2025)
Death is a natural occurrence which happens to all living things. In cases of sudden death, it is a challenge for forensic experts to exclude unnatural causes. Sudden death is majorly caused by cardiovascular diseases such as myocardial infarction, or arrythmia. Other causes of cardiovascular deaths are associated with artery rupture such as aortic dissection or coronary artery rupture. Mortality caused by blunt chest trauma is up to 15%. Most cases of coronary artery rupture are marked with cardiac tamponade which leads to death if no prompt treatment is provided. Our case was an elderly lady who was brought in with death due to a fall from a height of approximately 3 meters. Complete forensic examination later revealed a coronary artery rupture which may be caused by a rupture either in the ventricular muscle or the coronary artery itself. Death due to a cardiovascular event is common due to several reasons, especially when patients aren’t provided with prompt treatment. When compared with imaging studies, direct visualization using conventional forensic examination remains superior in evaluating organ or tissue damage. Keyword: coronary artery rupture; haemo-pericardium; left anterior descending artery